2015
DOI: 10.20319/lijshls.2015.s11.139150
|View full text |Cite
|
Sign up to set email alerts
|

Nano-Fe and MWCNTS Based Non-Enzymatic Sensor for Determination of Glucose in Seruum

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…In literature, it has been demonstrated that modifying the electrode's surface with MONs improves both the electrocatalytic performance and the analytical parameters for UA determination. Glassy carbon electrodes (GCE), carbon paste electrodes (CPE), and screen-printed electrodes (SPE) are generally used for this purpose due to their simple operation, low operating cost, and easy surface modification with graphene oxide (rGO), 51 carbon nanotubes (CNTs), 52,53 NPs, 54 MONs 55 bi-MONs, 56 semiconductor polymers, 57,58 doped metal oxide, 59 molecularly printed polymer, 60 metal-organic frames (MOF), 61 and nanoresins. 62 Glassy carbon electrodes (GCE) are commonly used for the electrochemical analysis of UA due to their wide working potential range, rapid electron transference, rapid response, and reusable surface by polishing.…”
mentioning
confidence: 99%
“…In literature, it has been demonstrated that modifying the electrode's surface with MONs improves both the electrocatalytic performance and the analytical parameters for UA determination. Glassy carbon electrodes (GCE), carbon paste electrodes (CPE), and screen-printed electrodes (SPE) are generally used for this purpose due to their simple operation, low operating cost, and easy surface modification with graphene oxide (rGO), 51 carbon nanotubes (CNTs), 52,53 NPs, 54 MONs 55 bi-MONs, 56 semiconductor polymers, 57,58 doped metal oxide, 59 molecularly printed polymer, 60 metal-organic frames (MOF), 61 and nanoresins. 62 Glassy carbon electrodes (GCE) are commonly used for the electrochemical analysis of UA due to their wide working potential range, rapid electron transference, rapid response, and reusable surface by polishing.…”
mentioning
confidence: 99%